Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s10934-014-9877-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and kinetic behavior of supported copper oxide catalysts on almond shell-based activated carbon for oxidation of toluene in air

Abstract: Dispersed copper oxide nano-catalysts supported on almond shell-based activated carbon were prepared for catalytic oxidation of toluene in air. The response surface methodology was used to express the catalyst removal efficiency in terms of catalyst metal loading and calcination temperature. Catalyst activity increased with both increasing calcination temperature and metal loading. Calcination temperature had a significant effect on the catalyst activity only at high metal loadings. Two different catalyst prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…Fig.17a indicates that addition of lanthanum and copper oxides to the alumina support reduces the catalyst activity for complete oxidation of toluene despite the surface modification caused by simultaneous addition of lanthanum and copper. Activity of copper oxide for total oxidation of toluene is higher than other metal oxides as reported in the literature [4]. Compared with other La-Cu/AlSE bimetallic catalysts, therefore, La2-Cu6/AlSE had the highest activity for oxidation of toluene in the humid air.…”
Section: Characterization Of Bimetallic Catalystsmentioning
confidence: 57%
See 1 more Smart Citation
“…Fig.17a indicates that addition of lanthanum and copper oxides to the alumina support reduces the catalyst activity for complete oxidation of toluene despite the surface modification caused by simultaneous addition of lanthanum and copper. Activity of copper oxide for total oxidation of toluene is higher than other metal oxides as reported in the literature [4]. Compared with other La-Cu/AlSE bimetallic catalysts, therefore, La2-Cu6/AlSE had the highest activity for oxidation of toluene in the humid air.…”
Section: Characterization Of Bimetallic Catalystsmentioning
confidence: 57%
“…Studies reported in the open literature suggest the negative effect of feed humidity on the catalyst activity. Water vapor is an end product in the oxidation of VOCs and could also be present in a humid feed [4]. It has been reported that the conversion of toluene decreased with increasing relative humidity in the feed due to the competition between water vapor, carbon dioxide, and toluene for adsorption on the metal oxides [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a need to develop economically viable techniques to effectively remove these pollutants. Catalytic oxidation is recognized as one of the most effective methods to reduce the atmospheric concentrations of VOCs [29][30][31]. Among the various approaches, catalytic oxidation is the most promising for this purpose due to advantages, which include high efficiency, low operating temperature, and no secondary pollution.…”
Section: Catalytic Oxidation Of Volatile Organic Compoundsmentioning
confidence: 99%
“…The performance of the catalyst toward the oxidation of VOCs depends on the physicochemical properties and morphology of the catalysts, the operating conditions, and the type and composition of the inlet gas stream [67][68][69]. Esmaeilirad et al, [70] have suggested that humidity could negatively affect the catalyst activity and the decomposition of the VOCs.…”
Section: Introductionmentioning
confidence: 99%